De novo fatty acid synthesis at the mitotic exit is required to complete cellular division - Scaglia, Natalia (2014)
Although the regulation of the cell cycle has been extensively studied, much less is known about its coordination with the cellular metabolism. Using mass spectrometry we found that lysophospholipid levels decreased drastically from G2/M to G1 phase, while de novo phosphatidylcholine synthesis, the main phospholipid in mammalian cells, increased, suggesting that enhanced membrane production was concomitant to a decrease in its turnover. In addition, fatty acid synthesis and incorporation into membranes was increased upon cell division. The rate-limiting reaction for de novo fatty acid synthesis is catalyzed by acetyl-CoA carboxylase. As expected, its inhibiting phosphorylation decreased prior to cytokinesis initiation. Importantly, the inhibition of fatty acid synthesis arrested the cells at G2/M despite the presence of abundant fatty acids in the media. Our results suggest that de novo lipogenesis is essential for cell cycle completion. This "lipogenic checkpoint" at G2/M may be therapeutically exploited for hyperproliferative diseases such as cancer.